Advancing surgical proficiency: insights from the 7th UiTM basic laparoscopic skills workshop - Khalid, Shahril; Osman, Nora Julianna; Mohd Aripin, Yahya; Ramzi Yusof, Ahmad
The 7th UiTM Basic Laparoscopic Skills Workshop held at Hospital Al Sultan Abdullah Puncak Alam on 6th and 7th December 2023, showcased an established platform for surgical trainees and medical officers to build their understanding and skills in laparoscopic surgery. With a primary focus on cultivating a strong foundation in laparoscopic surgery, the workshop provided participants with comprehensive knowledge and hands- on experience essential for advancing their surgical proficiency.